Modelling Software-Defined Networking: Software and hardware switches. (15th November 2018) - Singh, Deepak; Ng, Bryan; Lai, Yuan-Cheng; Lin, Ying-Dar; Seah, Winston K.G.
Abstract: In Software-Defined Networking (SDN), a switch is a forwarding device that moves data packets in a network. A software switch handles forwarding functions in software and thus cannot forward packet at line speed while a hardware switch leverages optimised forwarding hardware to forward packets at line speed. However, there has been very little research in the literature to help network engineers understand the tradeoffs in choosing one over the other. In this paper, we develop a unified queueing model for characterizing the performance of hardware switches and software switches in SDN. The unified queueing model is an analytical tool for engineers to predict delay, packet loss and throughput in their SDN deployments. Existing queueing models of SDN have focused on performance analysis of software switches, while our work presented herein is the first to present a unified analysis of hardware and software switches. Our proposed models exhibit errors below 5% compared to simulation. Between a hardware and software switch, the evaluation shows that a hardware switch achieves an average 80% lower delay and up to 100% lower packet loss probability compared to a software switch. The more a hardware switch involves the controller for decisioning, the lower the gains in terms of packet delays through the switch. Graphical abstract: Highlights: We propose a unified queues model for hardware and software SDN switches. Hardware switches achieve up to 80% lower delay and 100% lower packet loss probability compared to software switches. The more a hardware switch involves SDN controller for decisioning, the overall delay is lower compared to a software switch.